Role of Remote Sensing and Geographical Information System in Environmental Impact Assessment of Developmental Projects for Environmental Management (International Journal of Scientific Research and Management (IJSRM), 2016)
The fast growth in population, urbanization, change in land use pattern in developing countries have resulted in damage of historical, biological, archeological, aesthetic, visual impacts and pollution in land, water, air and noise. There are needs of a tool which can be capable of complex analysis and produce an alternative plan. Therefore Remote Sensing and Geographical Information System (GIS) are the latest technologies or support system or tool which will produce much more accurate results and perform various geographic analyses even in complex situations. Environmental Impact Assessment (EIA) is a less accurate and time consuming because it has more dependant and independent variables which have to be taken in to account such as Land use, land price, population density, socio-economic level, road accessibility, railway accessibility, air quality, ground water quality, noise level, biological content, historical value, archeological and visual importance etc. Remote Sensing and GIS technique is more comfortable, easy and accurate and complete the EIA of any proposed developmental activity in less time. EIA require reports of potential impacts of any proposed activities. By utilizing GIS modeling tools, potential impacts can be predicted and included in the management and monitoring programs. GIS and remote sensing could be used in environmental monitoring for Land use / Land cover analysis, wetland assessment and ground water modeling, habitat mapping, disaster management etc. Thus, Remote Sensing and GIS techniques play a significant role in Environment Impact Assessment process for the proper management of environment